2005
DOI: 10.1093/jat/29.5.275
|View full text |Cite
|
Sign up to set email alerts
|

Papain: A Novel Urine Adulterant*

Abstract: The estimated number of employees in the United Stated screened annually for illicit drugs is approximately 20 million, with marijuana being the most frequently abused drug. Urine adulterants provide an opportunity for illicit drug users to obtain a false-negative result on commonly used primary drug screening methods such as the enzyme multiplied immunoassay technique and the fluorescence polarized immunoassay technique (FPIA). Typical chemical adulterants such as nitrites are easily detected or render the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Burrows et al [18] mentioned that urine should be reported as adulterated if the pH was <3 or >11. In this study, only one adulterated cases were found.…”
Section: Discussionmentioning
confidence: 99%
“…Burrows et al [18] mentioned that urine should be reported as adulterated if the pH was <3 or >11. In this study, only one adulterated cases were found.…”
Section: Discussionmentioning
confidence: 99%
“…In a study related to this method, it has been found that 84% of urine samples were recollected because of low creatinine level and 20% of samples had a pH level out of the normal range (17). In addition to water, urinary adulteration may be tried using sodium bicarbonate, diuretics, and drugs containing salicylates (5). (1,2,(5)(6)(7)9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to water, urinary adulteration may be tried using sodium bicarbonate, diuretics, and drugs containing salicylates (5). (1,2,(5)(6)(7)9). High demand in this field has led to development of commercial kits specific to the substance used by the individual.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those incubated in the presence of 20 -100 µg of protease per mL of urine did not allow the determination of neither endogenous nor recombinant EPO. These results demonstrate that the addition of small amounts of proteases during doping control sample collection, e.g., by introducing a water soluble "rice grain" containing proteases, can alter urine specimens and complicate or even impede the analysis for peptide hormones such as EPO as well as low molecular weight target analytes [2] for sports drug testing purposes.…”
Section: Effect Of Proteases On Conventional Epo Drug Testing Assaysmentioning
confidence: 98%
“…As urine specimens are not fortified with protease inhibitor cocktails immediately after sampling, proteases can digest endogenous as well as recombinant EPO and other renally excreted peptide hormones and make them invisible for commonly employed drug testing assays [1,6,8,9,21]. The issue of urine manipulation has frequently been discussed in doping controls but also in workplace testing, and numerous agents and substitution tools are available via the Internet announcing options to pass drug tests for a variety of drugs of abuse [2,24,25]. In the present study, the possibility of manipulating doping control urine samples using proteases was investigated by analyzing EPO-spiked urine specimens analyzed using conventional electrophoretic EPO test assays.…”
mentioning
confidence: 99%